Equal Time : Television and the Civil Rights Movement - Bodroghkozy, Aniko, 1960- (Book collections on Project MUSE., 2012)
This work explores the crucial role of network television in reconfiguring new attitudes in race relations during the civil rights movement. The book provides an analysis which makes us think about the relationship between the media and the civil rights movement.